2020
DOI: 10.1101/2020.04.20.051334
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

A neural representation of invisibility: when stimulus-specific neural activity negatively correlates with conscious experience

Abstract: 24Although visual awareness of an object typically increases neural responses, we 25

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
2

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 58 publications
0
1
0
Order By: Relevance
“…However, this is not always the case. Recent work demonstrated that under some circumstances, the exact opposite can be found (Matthew J Davidson, Mithen, Hogendoorn, vanBoxtel, & Tsuchiya, 2020;Merten & Nieder, 2012).…”
Section: Single Neuronal Activity Correlates With Attention and Conscmentioning
confidence: 99%
“…However, this is not always the case. Recent work demonstrated that under some circumstances, the exact opposite can be found (Matthew J Davidson, Mithen, Hogendoorn, vanBoxtel, & Tsuchiya, 2020;Merten & Nieder, 2012).…”
Section: Single Neuronal Activity Correlates With Attention and Conscmentioning
confidence: 99%